Marketing for Sustainable Tourism - Martini, Umberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The aim of the Special Issue is to discuss the main current topics concerning marketing for sustainable tourism with reference to territories (i.e., tourism destinations, protected areas, parks and/or natural sites, UNESCO World Heritage Sites, rural regions/areas, etc.) and tourism enterprises and/or organisations (i.e., destination management organisations, hospitality enterprises, restaurant enterprises, cableway companies, travel agencies, etc.). In destinations where natural resources are pull factors for tourism development, the relationships among local actors (public, private, and local community), as well as marketing choices, are essential to develop sustainable tourism products. To this end, the Special Issue encourages papers that analyse marketing strategies adopted by tourism destinations and/or tourism enterprises to avoid overtourism, to manage mass sustainable tourism (as defined by Weaver, 2000), and to encourage and promote sustainable tourism in marginal areas or in territories suffering lack of integration in the tourism offer. Special attention will be given to contributions on the best practices to manage territories and/or enterprises adopting sustainable marketing strategies.